Heritage, identity and value: Ida's Valley, Stellenbosch - Ontong, Tyrone Gregory (School of Architecture, Planning and Geomatics, 2017)
Heritage sites, inclusive of cultural landscapes, are understood to derive their significance from perceptions of beauty, sense of place and, when it has been impacted by humans, its genius loci and tangible qualities and the overlay of their intangible associations. In order for a site to be recognized concurrence of an Authorised Heritage Discourse whose content is constructed by academics and professionally trained heritage experts and an Autochthonous Discourse defined and expressed by laypersons, occupying or having an association with the site or sites. When Ida's Valley Cultural Landscape underwent processes of identification and declaration (formal process) as a National Heritage Site in 2008 the assumption was that there was consensus between the two views, the Authorized Heritage Discourse and the Autochthonous Discourse. The hypothesis, then, in the case of Ida's Valley Cultural Landscape which lies just beyond the limits of the town, Stellenbosch, was that there was agreement between the AHD and the AD. The question that arose was whether the two readings of heritage value aligned and whether there really was agreement in terms of the significance of the site and the values it represented. This is found not to be the case. Concerns were raised regarding the manner in which the public participation process was handled, the content of the statement of significance around issues of identification, identity and, consequently, its impact on the idea of value. In addition, the issues of land for development, the locus of land ownership and the subsequent value and universal acceptance were placed under scrutiny and severely criticized by the local public and community groups. The conclusion was that there was no agreement between the two positions. The dissertation describes the exploration of these tensions.